Pediatric Cochlear Implant Mapping Via Telepractice. - Hughes, Michelle L.; Goehring, Jenny L.; Miller, Margaret K.; Robinson, Sara N. (Perspectives of the ASHA Special Interest Groups, 2016)
Several studies have empirically examined the feasibility and outcomes of remote programming for adults with cochlear implants. Results indicate that equivalent programming levels can be obtained in both the remote and in-person conditions, suggesting that distance technology is a viable alternative to traditional in-person programming methods. Young children, however, require different audiological testing methods to obtain the behavioral responses necessary for speech-processor programming. No studies have empirically evaluated the use of remote programming with the behavioral methods specific to testing young children. Further, young children present additional challenges to behavioral testing (e.g., ability to condition or cooperate) that can lead to the need for additional visits beyond those required for regular programming. This paper describes the potential benefits of remote programming over those achieved for adults, and describes the study design and preliminary results from our current study aimed at validating the use of remote processor programming for young children with cochlear implants (CIs).